Hair Stylists as Lay Health Workers: Perspectives of Black Women on Salon-Based Health Promotion. (1st April 2022) - Palmer, Kelly N. B.; Okechukwu, Abidemi; Mantina, Namoonga M.; Melton, Forest L.; Kram, Nidal A-Z.; Hatcher, Jennifer; Marrero, David G.; Thomson, Cynthia A.; Garcia, David O.
Lay health workers (LHWs) have been effective in delivering health promotion to underserved, vulnerable populations. Hair stylists are well positioned to serve as LHWs in addressing health disparities among Black women in the U.S. The purpose of this qualitative study was to explore the extent to which hair stylists influence their Black female clients and clients' preferences for their stylist's role in salon-based health promotion programming. Eight virtual platform focus groups were conducted with Black women (n = 39) who receive hair care services from a licensed hair stylist across the U.S. Most participants had a college degree (89.8%), health insurance (92.3%), a primary care provider (89.7%), and the majority had at least one chronic disease (56.4%). Participants reported higher potential for influence related to level of trust in the stylists and for stylists they find relatable and credible. Trust, relatability, and credibility were further determined by racial and gender congruence. Client interviewees felt stylists should model healthy behaviors and reported they may not be receptive to stylist-delivered health promotion out of the context of a hair-health connection. In this sample of well-educated clients, there was an expressed preference for stylists to provide referral to healthcare professionals or solicit experts for health topics out of the scope of haircare rather than guide the health promotion efforts themselves. Findings from this study can inform future development of acceptable salon-based, stylist-led health promotion programs that partner stylists with health experts to deliver health promotion.